Transdiagnostic treatment of emotional disorders for women with multiple sclerosis: a randomized controlled trial - Nabi Nazari; Akram Aligholipour; Masoud Sadeghi (BMC, 2020)
Abstract Background Multiple sclerosis (MS) is a chronic, unpredictable, neurodegenerative disease, significantly associated with psychological, behavioral, cognitive, and emotional consequences. MS is more common in females than males and frequently affects women during their reproductive years. Despite the frequent mental disorders, comorbidities, and emotional problems in People with MS (PwMS), these conditions are too often underdiagnosed and undertreated. Objective This study aimed to examine the efficacy of a group format of the Unified Protocol (UP) for the Transdiagnostic treatment of depression and anxiety disorders in females with MS. Methods In the present study, Sixty-four adult females diagnosed with MS were randomized to either the UP (n = 32) or treatment-as-usual conditions. The assessment protocol included semi-structured clinical interviews and self-reports evaluating diagnostic criteria, depression, anxiety and worry symptoms, emotional regulation, and affectivity. Results Repeated measure analysis of variance (ANOVA) revealed that the UP significantly improved depression scores [Cohen's d = − 2.11, 95% CI (− 2.72, − 1.50)], anxiety scores [Cohen's d = − 3.34, 95% CI (− 4.01, − 2.58)], positive and negative affect scale (PANAS)-positive affect scores [Cohen's d = 1.46, 95% CI (1.46, 2.01)], PANAS-negative affect scores [Coen's d = − 2.21, 95% CI (− 2.84, − 1.60)], difficulties emotion regulation scale scores [Cohen's d = 1.40, 95% CI (− 0.87, − 0.03)], and Worry scale scores [Cohen's d = − 0.45, 95% CI (− 0.95, − 0.04)] at the end of treatment relative to compared to the control condition. Also, treatment gains were maintained at the three-month follow-up (p < 0.001). Conclusion The findings provide the support that the UP could be an additional efficient psychological treatment for females with MS. ISRCTN Number: ISRCTN95459505.